Post-operative management of trabeculectomy in the first three months - Ian Murdoch (Community Eye Health Journal, 2012)
A successful trabeculectomy is a stable surgical fistula. The one thing required to keep a fistula patent (open) is flow. The principal and most challenging complication is scarring; however, other complications may occur, as outlined in this article.